2021
DOI: 10.1007/s00426-020-01432-y
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of filler items in the response time concealed information test

Abstract: The response time concealed information test (RT-CIT) can reveal that a person recognizes a relevant (probe) item among other, irrelevant items, based on slower responding to the probe compared to the irrelevant items. Therefore, if this person is concealing the knowledge about the relevance of this item (e.g., recognizing it as a murder weapon), this deception can be unveiled. Adding familiarity-related filler items to the task has been shown to substantially increase the validity of the method, but assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Nontarget-side fillers are control-referring expressions (e.g., the words “unfamiliar” or “irrelevant”) and have to be categorized with the same key as the probe and the controls. Fillers do not serve any diagnostic purpose, but their inclusion increases probe-control differences, thereby also increasing diagnostic efficiency based on these differences (for details, see Lukács & Ansorge, 2021; Lukács et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nontarget-side fillers are control-referring expressions (e.g., the words “unfamiliar” or “irrelevant”) and have to be categorized with the same key as the probe and the controls. Fillers do not serve any diagnostic purpose, but their inclusion increases probe-control differences, thereby also increasing diagnostic efficiency based on these differences (for details, see Lukács & Ansorge, 2021; Lukács et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, from another perspective, a series of studies shows that more cognitively demanding RT-CIT designs (e.g., increased number of different items in the task) increase probe-control differences (Hu et al, 2013; Lukács & Ansorge, 2021; Verschuere et al, 2015; Visu-Petra et al, 2013). This could also imply that if participants can perform the task more easily after practicing it for some time, the decreased cognitive demand may lead to decreased probe-control differences.…”
Section: Test Length Effect On Probe-control Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the Lukács, Kleinberg, et al (2017) study confirmed this reasoning. Also, a follow-up study (Lukács & Ansorge, 2021) provided strong evidence that the meaning of the fillers matters: reversing key mapping (unfamiliarity-related fillers categorized together with targets), as well as using neutral (e.g., object name) or pseudoword fillers, both reduced, or even obliterated, the enhancing effect of fillers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during the main task there was no header in either of our protocols.6 The smaller proportion (three to six) of important relative to unimportant fillers is intended to keep 'target-side' items (i.e. the target and items to be categorized with the same key as the target) less frequent than the rest of the items, thereby keeping the target (or all target-side items) more rare or even unique among all used items, since this relative rarity is assumed to contribute to the response conflict in case of probes: For more detailed explanation and empirical evidence, seeLukács & Ansorge (2021).…”
mentioning
confidence: 99%